2004
DOI: 10.1152/ajpregu.00143.2003
|View full text |Cite
|
Sign up to set email alerts
|

Differential control over postganglionic neurons in rat cardiac ganglia by NA and DmnX neurons: anatomical evidence

Abstract: . Differential control over postganglionic neurons in rat cardiac ganglia by NA and DmnX neurons: anatomical evidence. Am J Physiol Regul Integr Comp Physiol 286: R625-R633, 2004. First published November 26, 2003 10.1152/ajpregu.00143. 2003.-In previous single-labeling experiments, we showed that neurons in the nucleus ambiguus (NA) and the dorsal motor nucleus of the vagus (DmnX) project to intrinsic cardiac ganglia. Neurons in these two motor nuclei differ significantly in the size of their projection fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 30 publications
3
52
0
Order By: Relevance
“…The parasympathetic innervation of the rat heart is derived from preganglionic neurons in the medulla oblongata projecting axons in the vagus nerve to postganglionic neurons in the intracardiac ganglia (Cheng and Powley 2000;Cheng et al 1999Cheng et al , 2004. Previous studies have demonstrated that parasympathetic intracardiac neurons in rats and guinea-pigs can be classified into different subpopulations on the basis of their neurochemistry (Richardson et al 2003;Steele et al 1994), suggesting that intrinsic cardiac neurons may be chemically coded, as has been described for other neurons in the autonomic nervous system (Benarroch 1994;Furness et al 1992Furness et al , 1989Anderson 1995, 1997;Hökfelt 1991;Lundberg et al 1982).…”
Section: Introductionmentioning
confidence: 88%
“…The parasympathetic innervation of the rat heart is derived from preganglionic neurons in the medulla oblongata projecting axons in the vagus nerve to postganglionic neurons in the intracardiac ganglia (Cheng and Powley 2000;Cheng et al 1999Cheng et al , 2004. Previous studies have demonstrated that parasympathetic intracardiac neurons in rats and guinea-pigs can be classified into different subpopulations on the basis of their neurochemistry (Richardson et al 2003;Steele et al 1994), suggesting that intrinsic cardiac neurons may be chemically coded, as has been described for other neurons in the autonomic nervous system (Benarroch 1994;Furness et al 1992Furness et al , 1989Anderson 1995, 1997;Hökfelt 1991;Lundberg et al 1982).…”
Section: Introductionmentioning
confidence: 88%
“…In contrast, DMNX neurons have nonmyelinated axons, show little or no respiratory- and cardiac-modulation, have smaller effects on HR, and possibly stronger dromotropic (decreases in A-V nodal conduction) and inotropic (decreases in contractility) effects [99, 100, 109]. NA and DMNX neurons have been reported to innervate distinct populations of neurons within cardiac ganglia, consistent with different functional roles [110]. …”
Section: Direct Assessment Of Cardiovagal Activity and Mechanisms Of mentioning
confidence: 99%
“…The structural and functional alterations in every site of the arterial baroreflex arc are responsible for the T2DM-induced impairment of the arterial baroreflex sensitivity. Some previous studies have shown that parasympathetic cardiac neurons in the nucleus ambiguus in the brainstem extensively project to the ICG (1,9,10). More importantly, the arterial baroreflex control of the heart rate is almost totally abrogated when domoic acid lesion of the nucleus ambiguus stops the above projection to the ICG (11).…”
mentioning
confidence: 96%